PENGARUH PENGGUNAAN BUKU MUTABAAH YAUMIYAH TERHADAP PEMBENTUKAN KARAKTER SISWA DI SALAFIYYAH ULA TAHFIZH UMMUL QURO - Fiona Permita; Iwan Siswanto (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of using the mutaba’ah yaumiyah book on the character development of students at Salafiyyah Ula Tahfizh Ummul Quro. Character education is an important aspect in facing various social challenges; therefore, effective and measurable strategies are needed for character development, one of which is through daily habituation using the mutaba’ah yaumiyah book. This research employs a quantitative approach with a descriptive correlational design. The sample consisted of 79 students selected using simple random sampling. Data collection techniques included questionnaires, observation, and documentation, while data analysis was conducted using Pearson Product Moment correlation and simple linear regression with the assistance of SPSS. The results show a strong and positive relationship between the use of the mutaba’ah yaumiyah book and students’ character development, with a correlation coefficient of 0.635 and a significance value of 0.000 < 0.05. In addition, the regression results indicate that the mutaba’ah yaumiyah book contributes 40.3% to students’ character development. The novelty of this study lies in its quantitative measurement of the effectiveness of the mutaba’ah yaumiyah book as an instrument for character development and evaluation in a tahfizh-based elementary school.